O032/#771 Circulating HPV cell-free DNA in cervical cancer. (4th December 2022) - Mittelstadt, Suzana; Schroeder, Christopher; Kelemen, Olga; Jakob, Admard; Gschwind, Axel; Koch, André; Wörz, Sarah; Oberlechner, Ernst; Hoffmann, Sascha; Engler, Tobias; Andress, Jürgen; Neis, Felix; et al.
Abstract : Objectives: Human papillomavirus (HPV) related cervical cancer is the fourth most frequent cancer in women worldwide. Currently patient follow-up and therapy monitoring is solely based on clinical examination and cross-sectional imaging. The aim of this study was to investigate the potential use of HPV cell-free circulating DNA (cfDNA) in plasma samples of patients with cervical cancer. Methods: In this proof-of-concept study HPV cfDNA levels were measured using a highly sensitive Next-Generation-Sequencing-based approach targeting a panel of 13 high-risk HPV-types. cfDNA sequencing was compared to HPV testing in corresponding paraffin embedded tumor sample. Sequential plasma samples were taken from four patients receiving primary chemoradiation. Results: A total of 71 blood samples was collected from n=35 patients. HPV cfDNA was successfully detected in 25/35 (71%) patients. A significant correlation between tumor burden and HPV cfDNA detection was observed: while HPV cfDNA was detectable in most patients (20/22) with locally advanced or metastatic disease, detection was successful in only 5/13 patients with early-stage disease (p=0.001). HPV-types detected in plasma samples matched results from tumor tissue HPV testing. Sequential sampling showed a dynamic decrease of HPV cfDNA levels in line with treatment response in all patients. Conclusions: In this proof-of-concept study we were able to detect HPV cfDNA in primary and recurrent cervical cancer. Our findings may hold potential to develop a powerful and easily accessible tool in cervical cancer management.